Effects of External Water Pressure Reduction Coefficient on Parameters for High-Pressure Water injection test in Deep Boreholes of Pumped Storage Power Stations - YANG Wenchao; FAN Xinyu; REN Chao; SONG Minggang; CHEN Guojiang (工程科学与技术)
ObjectiveThe accuracy of high-pressure water injection test parameters in deep boreholes is crucial for the construction of pumped storage power stations. Currently, conventional computing methods for water injection test parameters remain used for high-pressure scenarios, leading to significant errors in deep borehole applications. This paper optimizes the calculation of additional hydraulic pressure by introducing an external water pressure reduction coefficient, thereby enhancing the reliability of deep borehole high-pressure water injection test parameters and providing more reliable guidance for engineering design.MethodsFirstly, the calculation method stipulated in current specifications is analyzed. By examining three groundwater level scenarios: above the test section, within the test section, and below the test section, it identifies that the additional hydraulic pressure calculation is based on the assumption that "the external water pressure exerted by the borehole water on the test section equals its full hydrostatic pressure." This overestimated external water pressure is the primary cause of parameter errors in deep-borehole high-pressure water injection tests. For optimization, an external water pressure reduction coefficient is introduced to recalibrate the additional hydraulic pressure calculation under all three groundwater conditions. This adjustment brings the external water pressure closer to actual field conditions and yields more rational computational parameters. Finally, the method is validated through a case study at a pumped storage power station. The reduction coefficient is derived by interpolating permeability rates from water injection tests in deep boreholes. The revised approach calculates key parameters, including permeability rate and splitting pressure under high-pressure water injection test conditions, and demonstrates significant improvements compared to standard calculation results.Results and Discussions The current specification for the pressure calculation baseline in high-pressure water injection tests is based on the assumption that the external water pressure reduction coefficient is not considered, which may lead to non-negligible errors in deep borehole parameter calculations. According to the revised additional hydraulic pressure calculation formula incorporating external water pressure reduction coefficient, when the borehole water level is above or within the test section, additional hydraulic pressure is influenced by external water pressure reduction coefficient. Generally, additional hydraulic pressure calculated with external water pressure reduction coefficient is greater than that specified in current standards, and shows a negative correlation with external water pressure reduction coefficient. When the groundwater level is below the test section, additional hydraulic pressure remains unaffected by external water pressure reduction coefficient. The calculation formula is applied to the deep hole of a pumped storage power station in Shaanxi province and compared with the standard method. The results show that: In intact to moderately intact granite formations, the failure pattern of the P-Q curve in high-pressure water injection tests deviates from the conventional five-type classification. Instead, it exhibits a composite characteristic of "laminar flow in the initial phase and cracking behavior in the later phase". The P-Q-t curve demonstrates distinct stages demarcated by the splitting pressure: during the first stage, incremental pressure increases yield no significant flow rate growth, while the second stage features a brittle-failure pressure drop accompanied by a sharp flow surge. Permeability rates calculated via the standard method for conventional water injection tests range 0.03 Lu ~ 3.85 Lu (average: 0.20 Lu). In contrast, the reduction coefficient method yields 0.01 Lu ~ 1.26 Lu (average: 0.11 Lu), representing reductions of 3.7% ~ 72.8% (average: 44.1%) compared to the standard method. The reduction magnitude increases with borehole depth, notably reaching 71.1% for average permeability in powerhouse sections. The water permeability of high-pressure water injection test is 0.19Lu ~ 0.26Lu by standard method, and 0.12Lu ~ 0.14Lu by reducing coefficient method, which is 36.0% ~ 41.8% lower than the former. The ratio of the high-pressure water injection test to the conventional water injection test is 12.0 to 16.9 times, the water permeability of the high-pressure water injection test is much higher than that of the conventional one. The splitting pressure calculated by the standard method ranges from 5.52MPa to 7.81MPa, and the splitting pressure calculated by the reduction coefficient method ranges from 10.14MPa to 12.20MPa. The value of the splitting pressure obtained by the reduction coefficient method is much higher than that by the standard method. This study experimentally validates the impact of the external water pressure reduction coefficient on high-pressure water injection tests in intact to moderately intact granite formations, however this method is also feasible in other diverse geological strata.ConclusionsCompared to the standard method, the modified reduction coefficient approach enables more accurate characterization of rock mass permeability and fracturing pressure, thereby effectively mobilizing the rock's anti-seepage potential. This methodology provides critical guidance for optimizing designs and reducing project costs. The construction of pumped storage power stations is experiencing rapid expansion, accompanied by a prevailing trend of increasingly deeper boreholes, the accuracy of high-pressure water injection test parameters obtained from deep boreholes holds critical significance for pumped storage projects. It is strongly advised that external water pressure reduction coefficients be fully incorporated into high-pressure water injection test calculations for pumped storage power stations. By comparatively analyzing the impacts of both current code methods and the reduction coefficient method on engineering design, a more scientific balance between design safety and construction costs can be achieved, ultimately enhancing the quality of survey and design works for pumped storage power stations.